GENERAL PRINCIPLES OF SOL - GEL - Toygun, Safak; Konecoglu, Gulhan; Kalpakli, Yasemen (YILDIZ TECHNICAL UNIV, 2013)
The sol-gel synthesis based on the hydrolysis and condensation of molecular precursors is used to prepare a wide range of inorganic materials. The sol-gel technique is a very convenient method of obtaining both inorganic and hybrid organic-inorganic polymers. Basic advantage of this technique is carrying out the whole process at very gentle conditions. In contrast to solid-state processes, sol-gel processes offer the possibility to control the reaction pathways on a molecular level during the transformation of the precursor species to the final product. In this way, sol-gel processes enable the synthesis of nanoparticles with well-defined and uniform crystal morphologies and with superior purity and homogeneity. Sol-gel chemistry is a quite complex process, on the one hand due to the high reactivity of the metal oxide precursors towards water and the double role of water as ligand and solvent, and, on the other hand, due to the large number of reaction parameters that have to be strictly controlled (hydrolysis and condensation rate of the metal oxide precursors, pH, temperature, method of mixing, rate of oxidation, etc.) in order to provide good reproducibility of the synthesis protocol. Therefore, the main target of the present review is to explain the basic principles of sol- gel process and to evaluate the parameters that are effective in the sol- gel processes.
Keywords: Sol-gel; gelation; aging; drying; sintering; PHASE MICROEXTRACTION FIBERS; ELECTROCHROMIC COATINGS; THIN-FILMS; TIO2; MICROWAVE; OXIDE; NANOCRYSTALLINE; NANOPARTICLES; CALCINATION; MEMBRANES; Engineering